Comparative Study of Parental Pressure Between Male and Female Adolescent Students - Ashu Soni; Dr. Aruna Anchal (International Journal of Scientific Research in Science and Technology, 2024)
Adolescence is the period of transition from childhood to adulthood. During this period an individual go through physical and psychological development, also known as ‘puberty period’ which is associated with teenage years (13-19).W.H.O. has defined adolescents as individuals aged between in 10-19 years. Parental pressure is of screaming importance, expressly for the entire growth, Time management and development of adolescence. In future societies the majority of people will very often experience symptoms associated with stress and time management at some point.. This study describes the relation of students’ parental pressure with their gender. The study was conducted among secondary school students of Rewai District, which include two private and two government schools of same area. The numbers of respondents were 600. The findings revealed that there is a significant relation between Students parental pressure and their gender among secondary students in Government and Private schools. According to result female students having high parental pressure Relationships between variables were identified using Demographic data,  Mean, S.D., t-test, Statistical package for social science (SPSS) version 21.0 and correlation tests were used in the data analysis.
Keywords: Parental Pressure and Adolescents; SPSS; Demographic data